2017
DOI: 10.4172/2329-6488.1000268
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Factors that Impact Relapse Post-residential Addiction Treatment, a Six Month Follow-up from a Canadian Treatment Centre

Abstract: Although substance use disorder is a detrimental disease that negatively affects millions of Canadians each year, recovery is possible. Varying factors, however, may impact the likelihood of recovery after the affected individual completes treatment. Understanding the related factors associated with post-treatment outcomes would allow substance use disorder professionals to foster positive outcomes, and if appropriate, provide additional support for individuals in need. This study, therefore, examines the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
2
3
0
2
Order By: Relevance
“…Moreover, the results of this study suggest that the PUD who experienced low accessibility to drugs had a greater risk to relapse than the patients who appropriately accessed to required health treatments. This result is in line with the previous studies that confirmed that environmental risk factors increase the risk of relapse such as the increased availability and accessibility of drugs [19,21,34,35,37]. The results revealed that patients using multiple substances such as two to three substances were more likely to relapse than those only used one substance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the results of this study suggest that the PUD who experienced low accessibility to drugs had a greater risk to relapse than the patients who appropriately accessed to required health treatments. This result is in line with the previous studies that confirmed that environmental risk factors increase the risk of relapse such as the increased availability and accessibility of drugs [19,21,34,35,37]. The results revealed that patients using multiple substances such as two to three substances were more likely to relapse than those only used one substance.…”
Section: Discussionsupporting
confidence: 92%
“…In a study solely examining patient in residential treatment, abstinence rates were lower for those who had short stays (1-30 days) than those who had longer LOS. Similarly, individuals who attended a long term institutional treatment were found to be more likely to be abstinent at six months post-treatment compared to the short-term (three to six month) residential treatment program [35,36]. Moreover, the results of this study suggest that the PUD who experienced low accessibility to drugs had a greater risk to relapse than the patients who appropriately accessed to required health treatments.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Patients with education level up to secondary level were prevalent (30.2%) during psychotic disorders disease presentation. Our findings matched with other studies' results, according to which illiterate people had a higher proportion of substance users compared to educated people [25,26]. Secondary school students are more susceptible to substance users due to their curiosity and capitulate to aristocrat pressure to use substances.…”
Section: Discussionsupporting
confidence: 91%
“…Um estudo realizado na Ruanda, em 2021 15 , revelou resultados semelhantes em que o tempo de hospitalização foi significantemente associado à recaída e aqueles que são internados de um a três meses tiveram maior risco de recaída em comparação com os que foram hospitalizados por tempo superior a três meses. Estudos que examinam o tempo de permanência nas taxas de abstinência pós-tratamento encontraram relação direta entre a maior duração da estadia e as taxas de abstinência mais altas [16][17] .…”
Section: Discussionunclassified